Sifat Fisik, Kimia Dan Sensoris Yoghurt Kelapa Muda (Cocos nucifera L.) Dengan Penambahan Puree Buah Naga Merah (Hylocereus Polyhizus) - Canon, Fazril; Djarkasi, Gregoria S. S.; Langi, Tineke M. (Jurnal Teknologi Pertanian (Agricultural Technology Journal), 2023)
This study aims to determine the physical, chemical and sensory properties which include viscosity, total acid, pH, color grab test, taste, texture, aroma, color in young coconut yogurt with the addition of red dragon fruit puree. The research method used was a completely randomized design (CRD) method with 4 treatment levels of the proportions of young coconut meat and red dragon fruit puree namely A0 (300gr : 0%), A1 (300gr : 10%), A2 (300gr : 20%), A3 (300gr : 30%), and A4 (300gr : 40%) with 3 repetitions. The results showed that the average value of the viscosity test ranged from 17.87cp – 19.11cp, the total acid ranged from 0.17110% – 0.27717%, the pH ranged from 3 – 4, the preference level test used a hedonic scale which included from In terms of color, taste, aroma, texture, the average value for color ranges from 4.32 (neutral) – 5.80 (likes), aroma ranges from 3.48 (rather dislikes) – 4.52 (rather likes) , texture ranged from 4.12 (neutral) – 5.12 (rather like), taste ranged from 2.96 (rather dislike) – 4.28 (neutral).